Behavioral Biases in Financial Decision Making : Implications for Accounting and Economic Forecasting - Jean-Philippe Bonardi; Didier Sornette; Robert Danon (International Forum of Researchers and Lecturers, 2024)
Behavioral economics has highlighted how cognitive biases influence financial decisionmaking, often leading to suboptimal outcomes. This paper explores the impact of behavioral biases such as overconfidence, loss aversion, and herding behavior on accounting and economic forecasting. By reviewing empirical evidence from market behavior, the study assesses how these biases affect financial reporting, auditing practices, and economic predictions. The paper concludes with recommendations for accountants and economists to incorporate behavioral insights into their practices to improve decisionmaking and forecasting accuracy.